PENGARUH SUBTITUSI MILK CHOCOLATE DAN MARGARIN TERHADAP MUTU PISANG SALE GORENG LAPIS COKELAT - Hasni, Dian; Abubakar, Yusya’; Azhari, M. Rizky (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2021)
Pisang sale is a semi-moist food made from fresh bananas by drying and/or smoking with or without the addition of preservatives. In the city of Banda Aceh, a fairly well-known processed pisang sale is fried pisang sale with a large production volume. Coating pisang sale with chocolate is an innovation that can improve the quality and acceptance of pisang sale by consumers. This study aims to obtain the optimum formulation of chocolate coating material to be applied to fried pisang sale, as well as its effect on the physicochemical quality and sensory quality of the resulting chocolate-coated fried pisang sale. This study was conducted using a factorial Randomized Block Design with compound chocolate substitution factors of dark chocolate variants with milk chocolate (S) and the addition of margarine (M). Chocolate substitution consists of two levels, namely S1 = 10% (milk chocolate) and S2 = 20% (milk chocolate). The addition of margarine (M) consists of three levels M1 = 0%, M2 = 7.5% and M3 = 15% of the total weight of the dough. Repetition was carried out 3 times so that 18 experimental units were obtained. The analysis conducted was melting point analysis and organoleptic analysis including hedonic and descriptive tests. The results showed that the addition of margarine significantly affected the melting point (˚C) and panelists' acceptance of the aroma of pisang sale (descriptive), color (hedonic) and taste (hedonic) of the resulting chocolate fried pisang sale. The melting point of the resulting chocolate had an average temperature of 37.61˚C. Organoleptically, the aroma of pisang sale (descriptive) had a rather weak-neutral aroma, color and taste (hedonic) ranged from neutral to like. The taste of pisang sale was neutral (descriptive), had a rather strong chocolate taste (descriptive) and a neutral-like taste (hedonic).